Reversed scototaxis during withdrawal after daily- moderate, but not weekly-binge, administration of ethanol in zebrafish - Holcombe, Adam; Howorko, Adam; Powell, Russell A.; Schalomon, Melike; Hamilton, Trevor (My University, 2013)
Alcohol abuse can lead to severe psychological and physiological damage. Little is known, however, about the relative impact of a small, daily dose of alcohol (daily-moderate schedule) versus a large, once per week dose (weekly-binge schedule). In this study, we examined the effect of each of these schedules on behavioural measures of anxiety in zebrafish (Danio rerio). Adult wild-type zebrafish were administered either 0.2% ethanol on a daily-moderate schedule or 1.4% ethanol on a weekly-binge schedule for a period of 21 days, and then tested for scototaxis (preference for darkness) during withdrawal. Compared to a control group with no alcohol exposure, the daily-moderate group spent significantly more time on the light side of the arena (indicative of decreased anxiety) on day two of withdrawal, but not day 9 of withdrawal. The weekly-binge group was not significantly different from the control group on either day of withdrawal and showed no preference for either the light or dark zones. Our results indicate that even a small dose of alcohol on a daily basis can cause significant, though reversible, changes in behaviour.
Keywords: zebrafish; ethanol